DIRECTION OF STUDENTS TO NATIONAL CRAFT PROFESSIONS IN SCHOOL TECHNOLOGY EDUCATION - Shomirzayev Makhmatmurod Khuramovich (Journals Park Publishing, 2023)
The article describes in detail the essence of directing students to national craft professions in school technology education.
Keywords: national, profession, school, craft, hobby, student, technology, creativity, perspective, principle, tool.